PENGARUH CITRA MEREK DAN LOKASI TERHADAP MINAT BELI KONSUMEN COFFE CAPPUCINO SRIBU COFFE DI KOTA BENGKULU - Zacky Mubarok (UM. Bengkulu, 2026)
This study aims to determine the Influence of Brand Image and Location on Consumer Purchase Interest of Cappuccino Coffee at Sribu Coffee. This study uses a quantitative research type with a survey approach involving consumers of Cappuccino Coffee at Sribu Coffee who were selected using a survey method. Data collection through questionnaires that have been tested for validity and reliability, measuring the dimensions of Brand Image, Location and Purchase Interest indicators. Data analysis was carried out using descriptive statistics and multiple linear regression with the help of statistical software. The results show that there is no partial influence of Brand Image on Purchase Interest. In the Location Variable, a partial influence on Purchase Interest was found. Thus, Brand Image can only have a significant positive influence on Purchase Interest if combined simultaneously with Location. The implications of this finding provide insight for Sribu Coffee to develop more innovative flavors and develop product quality, as well as provide comfort and security for consumers. Key Words : Brand Image, Location, Buying Interest